Theoretical Studies on the Reaction Mechanism of Photocatalytic Degradation of Acetone - Bi, Hui-Min; Liu, Yan; You, Fu-Ying; Chai, Xing-Quan; Xie, Peng-Tao; Hu, Jun-Ping (Asian Journal of Chemistry, 2011)
The reaction mechanism of photocatalytic degradation of acetone by TiO2 was investigated by using B3LYP methods with the 6-311++G (3df, 3pd) basis sets and reaction channels were found. Geometries of the reactants, predicted that the intermediate product is CH3COOH, last products of reaction is CO2 and H2O. Intermediates, transition states and products were optimized and intrinsic reaction coordinate calculations were carried out. The calculated results successfully explained the conclusion of Huang's experimental study. From the view of bond length and energy analysis, the changes of chemical bonds in the reactions were discussed, the potential energy of the reaction was low, which will be helpful for the experimental research of the photocatalytic degradation of acetone.